Ferroptosis-associated lncRNA prognostic signature predicts prognosis and immune response in laryngeal squamous carcinoma: LncRNA signature predicts prognosis in laryngeal carcinoma - Dong, Yuan; Zhao, Kai; Qiu, Qibing; Zheng, Shikang; Zhang, Xiaoran; Liu, Jinjing; Xu, Haiming; Pan, Xiazhi; Liu, Mingbo (Cellular and Molecular Biology, 2023)
In order to construct a prognostic model of ferroptosis-related lncRNA associated with laryngeal carcinoma and to investigate its prognostic value, RNA sequencing, genomic mutation, and clinical data of laryngeal squamous carcinoma patients were collected from the TCGA database. Patients were randomly divided into train and test groups. Cox regression analysis and lasso regression analysis were performed on the data of patients in the training group, and their independent prognostic effect was validated in the test group and the whole cohort. Data from 123 laryngeal squamous carcinoma patients in the TCGA database were collected. According to previous literature, 484 ferroptosis-related genes were collected, and 912 ferroptosis-related lncRNAs were obtained by co-expression. Cox models suggested six lncRNAs involved in ferroptosis (AC083862.2, CYTOR, AC114296.1, LINC02768, GATA2-AS1, CTB-178M22.2). Patients were divided into high-risk and low-risk groups based on median risk scores. Kapkan-Meier survival curve results showed a statistical difference in survival between the high- and low-risk groups. Receiver operating characteristic curves and principal component analysis demonstrated the high accuracy of the model. Univariate and multifactorial Cox regression analyses and column plots demonstrated risk scores as independent prognostic factors. The distribution of prognostic marker risk scores was correlated with clinical staging. Immune infiltration studies suggested the model was associated with immune checkpoints and multiple immune functions. GATA2-AS1 was able to promote cell proliferation, cell migration, and cell invasion. This study identified six lncRNAs associated with ferroptosis in laryngeal squamous carcinoma as prognostic predictors, which may be promising biomarkers involved in the treatment of laryngeal squamous carcinoma.